ANALISIS KINERJA DENGAN METODE BALANCED SCORECARD PADA RSUD.S.K.LERIK KOTA KUPANG - Herny Ellen Djunina; Wehelmina M. Ndoen; Christien C. Foenay (Universitas Nusa Cendana, 2017)
This research aim to know the performance of RSUD S. K. Lerik Kota Kupang that measured byBalanced Scorecard approaching. The research method is case study, with analytical techniquereferring to Balanced Scorecard approaching, those are Financial Perspective, Customer Perspective,Internal Business Process Perspective and Learning And Growth Perspective. The results of theanalysis show that Financial Perspective as measured by the Economic Ratio is categorized as